The growth of meromorphic solutions for a class of higher-order linear differential equations - Liu, Ming-Sheng; Yuan, Chun-Ling (Applicable analysis, 2006)
In this article, the growth of meromorphic solutions for a class of higher-order linear differential equation with meromorphic coefficients is investigated by applying the method of value distribution, and some estimates for the hyper-order of their solutions are obtained. †Dedicated to Professor Wei Lin on the occasion of his 70th birthday.